2020
DOI: 10.1101/2020.12.08.416677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intranasal administration of SARS-CoV-2 neutralizing human antibody prevents infection in mice

Abstract: Prevention of SARS-CoV-2 infection at the point of nasal entry is a novel strategy that has the potential to help contain the ongoing pandemic. Using our proprietary technologies, we have engineered a human antibody that recognizes SARS-CoV-2 S1 spike protein with an enhanced affinity for mucin to improve the antibody’s retention in respiratory mucosa. The modified antibody, when administered into mouse nostrils, was shown to block infection in mice that were exposed to high titer SARS-CoV-2 pseudovirus 10 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Our studies of nAb STI-2020 previously demonstrated the protective efficacy of IN-administered antibodies in the context of SARS-CoV-2 preclinical models of pathogenesis 46 . Previous work in preclinical models of respiratory virus pathogenesis support the use of IN-administered IgG and IgA mAbs in prophylactic and therapeutic dosing regimens 24,[47][48][49][50] . In the current report, we described the protective effects of STI-9167 delivered by either the IN or the IV route to animals infected with WA-1 strain, Delta, or Omicron variants.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies of nAb STI-2020 previously demonstrated the protective efficacy of IN-administered antibodies in the context of SARS-CoV-2 preclinical models of pathogenesis 46 . Previous work in preclinical models of respiratory virus pathogenesis support the use of IN-administered IgG and IgA mAbs in prophylactic and therapeutic dosing regimens 24,[47][48][49][50] . In the current report, we described the protective effects of STI-9167 delivered by either the IN or the IV route to animals infected with WA-1 strain, Delta, or Omicron variants.…”
Section: Discussionmentioning
confidence: 99%
“…[212][213][214] This mode of administration may be particularly beneficial for respiratory pathogens, such as COVID-19; direct antibody deposition in the airway would bind to and neutralize SARS-CoV-2 virus particles and may enable a higher efficacy with a lower dose in inhibiting infections in the lung. [215][216][217] This technology is being evaluated for antibody therapeutics including monoclonals, [218][219][220][221][222] other modalities (nanobodies, [223][224][225] IgY 226,227 ), and possibly HIGs. 216…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, neither the nasal cavity nor lung areas showed signs of infection in EU126-M2 antibody-treated mice 7 days after virus dosing. Moreover, EU126-M2 proved to be stable in a nasal spray formulation for up to 2 weeks, at 37 • C. By August 2021, the company is preparing an Investigational New Drug application with the FDA for a clinical trial of the InvisiMask™ [91,92].…”
Section: Intranasal Delivery Of Therapeutics Against Covid-19 41 Nasal Delivery Of Antibodiesmentioning
confidence: 99%